The impact of environmental factors on the phytoplankton communities in the Western Pacific Ocean: HPLC-CHEMTAX approach - Zhang, Guicheng; Liu, Zishi; Zhang, Zhaoyi; Ding, Changling; Sun, Jun (Frontiers in Marine Science, 2023)
The distribution characteristics, biomass, and communities of phytoplankton in the western Pacific Ocean (WPO) were investigated using high-performance liquid chromatography (HPLC)-CHEMTAX analysis. The results revealed significant differences in the distribution of phytoplankton communities among different water masses in the WPO. Haptophytes were the dominant group, followed by Prochlorophytes, Cyanobacteria, Prasinophytes, and Diatoms. The distribution of phytoplankton communities was primarily determined by the level of nitrate, phosphate, and silicate, while temperature showed a negative correlation with major phytoplankton communities. In the 130°E section, the divergence caused by Halmahera Eddy (HE) and Mindanao Eddy (ME) provided the abundant nutrients, making them the primary environmental influence factor near the equator. This divergence brought relatively eutrophic deep seawater into the euphotic layer, resulting higher biomass of phytoplankton communities. In the 20°N section, the distribution of phytoplankton was mainly influenced by the invasion of Kuroshio Current and its offshore flow. Additionally, due to the low surface-to-volume ratios, microphytoplankton dominated the phytoplankton community in this section instead of nanophytoplankton or picophytoplankton. In summary, this study confirms previous findings on distribution characteristics of phytoplankton and provides new insights into the environmental and biological regulations of phytoplankton communities in the WPO.